Tangshen Formula Attenuates Diabetic Kidney Injury by Imparting Anti-pyroptotic Effects via the TXNIP-NLRP3-GSDMD Axis - Li, Nan; Zhao, Tingting; Cao, Yongtong; Zhang, Haojun; Peng, Liang; Wang, Yan; Zhou, Xuefeng; Wang, Qian; Li, Jialin; Yan, Meihua; Dong, Xi; Zhao, Hailing; et al. (Frontiers in Pharmacology, 2021)
We previously reported that Tangshen formula (TSF), a Chinese herbal medicine for diabetic kidney disease (DKD) therapy, imparts renal protective effects. However, its underlying mechanism remains unclear. Pyroptosis is a form of programmed cell death that can be triggered by the NLRP3 inflammasome. Recently, the association between the pyroptosis of renal resident cells and DKD was established; however, evidence is limited. This study aimed to investigate whether the kidney protective effects of TSF are related to its anti-pyroptotic effect. DKD rats established by right uninephrectomy plus a single intraperitoneal injection of STZ and HK-2 cells stimulated by AGEs were used. In vivo, TSF reduced 24-h-urine protein (24h-UP) of DKD rats and alleviated renal pathological changes. Meanwhile, the increased expression of pyroptotic executor (GSDMD) and NLRP3 inflammasome pathway molecules (NLRP3, caspase-1, and IL-1β), located in the tubules of DKD rats, were downregulated with TSF treatment. In vitro, we confirmed the existence of pyroptosis in AGE-stimulated HK-2 cells and the activation of the NLRP3 inflammasome. TSF reduced pyroptosis and NLRP3 inflammasome activation in a dosage-dependent manner. Then, we used nigericin to determine that TSF imparts anti-pyroptotic effects by inhibiting the NLRP3 inflammasome. Finally, we found that TSF reduces reactive oxygen species (ROS) production and thioredoxin-interacting protein (TXNIP) expression in AGE-stimulated HK-2 cells. More importantly, the colocalization of TXNIP and NLRP3 decreased with TSF, indicating that ROS-TXNIP may be the target of TSF. In summary, the anti-pyroptotic effect via the TXNIP-NLRP3-GSDMD axis may be an important mechanism of TSF for DKD therapy.